أهمية استخدام الطاقة المتجددة كبديل للطاقة التقليدية في العالم العربي - العيسوي، أحمد سعيد محمود محمد (جامعة بنها - كلية التجارة, 2019)
نظرا لمعاناة العالم العربي من تداعيات استخدام الطاقة التقليدية متمثلة في استنزافها أو ما يصدر عنها من ملوثات ضارة بالبيئة وصحة الأنسان، يتجه العالم في الوقت الراهن وخاصة العالم العربي إلي البحث عن طاقات متجددة تحد من استهلاك الطاقة وفي نفس الوقت تحافظ على البيئة وصحة الأنسان. وفي ضوء، ذلك تم التعرف على مصادر الطاقة المتجددة والتي تتمثل في طاقة الرياح، الشمسية، النووية، والمائية، والتحديات التي تقابلها وكيفية مواجهتها. وعليه توصلت الدراسة: بأن يشهد قطاع المتجددة في دول العالم العربي خلال الفترة القادمة توسعا ملحوظا على الرغم من التحديات التي يواجهها؛ كونه خيار الطاقة المستقبل الأفضل بالنسبة لتلك الدول. حيث لم يعد الاعتماد عليها استثمارا مرفها، بل أصبح ضرورة لابد منها اقتصاديا وبيئيا. لذا أوصت الدراسة: بأهمية تشجيع استخدام الطاقة المتجددة كجزء ضروري ضمن الخطط الاستراتيجية القومية للطاقة في الدول العربية خاصه الشمسية منها، وإنشاء مشروعات قومية لتخزين تلك الطاقة والاستفادة منها طوال السنة.
In view of the world's suffering from the effects of traditional energy use, which is depleted or released from harmful pollutants to the environment and human health, the world is currently searching for renewable energies that limit energy consumption and at the same time preserve the environment and human health. In light of this, the sources of renewable energy, which are wind, solar, nuclear, hydropower, and the challenges they face, have been identified and how to deal with them. Therefore, the study found that the renewable sector in the Arab world will witness a significant expansion in spite of the challenges facing it, as it is the best future energy option for these countries, as it is no longer an economic investment. Therefore, it recommended the Study to importance of encouraging the use of renewable energy as a necessary part of national energy strategic plans in the Arab countries, especially the solar ones, and the establishment of national projects to store and uses this energy throughout the year.
Keywords: التنمية المستدامة -- الطاقات المتجددة -- الأمن البيئي -- الوطن العربي